Downskilling: Changes in employer skill requirements over the business cycle - Alicia Sasser Modestino; Daniel Shoag; Joshua Ballance (Federal Reserve Bank of Boston, 2016)
Using a novel database of 82.5 million online job postings, we show that employer skill requirements fell as the labor market improved from 2010 to 2014. We find that a 1 percentage point reduction in the local unemployment rate is associated with a roughly 0.27 percentage point reduction in the fraction of jobs requiring at least a bachelor's degree and a roughly 0.23 percentage point reduction in the fraction requiring five or more years of experience. This pattern is established using multiple measures of labor availability, is bolstered by similar trends along heretofore unmeasured dimensions of skill, and even occurs within firm-job title pairs. We further confirm the causal effect of labor market tightening on skill requirements using a natural experiment based on the fracking boom in the United States as an exogenous shock to the local labor supply in tradable, non-fracking industries. These industries are not plausibly affected by local demand shocks or natural gas extraction technology, but still show fewer skill requirements in response to tighter labor markets. Our results imply this labor market-induced downskilling reversed much of the cyclical increase in education and experience requirements that occurred during the Great Recession.
Keywords: D22; E24; J23; J24; J63; 330; labor demand; skills; vacancies; unemployment; firm behavior